Is bilateral lung transplantation in pulmonary artery hypertension related to congenital heart disease a real therapeutic option? Experience of a national referral centre. (3rd October 2022) - Luna, R; Segura De La Cal, T; Alonso, R; Quezada, A; Real, I; Cortes, M; Sarnago Cebada, F; Velazquez, M; Lopez Gude, M; Escribano Subias, P; Gamez, P
Abstract: Background: Pulmonary arterial hypertension (PAH) affects almost 10% of patients with congenital heart disease, markedly worsening their prognosis. Bilateral lung or cardiopulmonary transplantation is therefore the last therapeutic option. The presence of underlying congenital heart disease (CHD) leads many of these patients directly to cardiopulmonary transplantation. However, this option is increasingly limited due to the shortage of organs and the high risk of the procedure. Purpose: Demonstrate that isolated bilateral lung transplantation (BLT) associated with repair of simple heart defects is an option that leads to good prognostic outcomes and adequate positive cardiac chamber remodelling. Methods: We retrospectively analysed the cases of PAH-CHD in our centre who underwent BLT from September 2010 to January 2022. Results: During the recorded time 12 of the 135 PAH-CHD patients followed in our unit were considered for transplantation. Six BLT were finally performed. The reasons for rejecting the option of transplantation in patients with congenital heart disease included, in addition to the usual ones (age, histocompatibility, comorbidities, ...) the presence of abundant collateral circulation or repeated thoracic interventions. Of the 6 patients who underwent transplantation of both lungs, the mean age was 39±10 years and 4 were women (66.6%). All of them had previous symptoms of heart failure, 4 of them presented recurrent supraventricular arrhythmias requiring ablation, one of them required stent implantation in the left coronary trunk due to extrinsic compression by the pulmonary artery trunk and another had presented threatening haemoptysis requiring embolization of bronchial branches. Regarding the aetiology of PAH-CHD, two of the patients had residual PAH after previous closure of the intracardiac defect years earlier and the remaining four patients (66.6%) had an incidental intracardiac shunt (2 ASD and 2 VSD). Both incidental ASD were closed in the main intervention. The course of the operation and immediate post-transplantation was similar to other PAH transplants, with a mean ICU stay of 10 days. All patients were discharged home and remain alive to date without recurrence of cardiovascular symptoms. On post-transplant echocardiographic re-evaluation, all patients had normalized right chambers in terms of both size and function (Table 1). Conclusion: Isolated bilateral lung transplantation is a real option for most cases of pulmonary arterial hypertension associated with congenital heart disease with simple or previously repaired defects. BLT in these patients is not accompanied by a higher rate of complications in the immediate postoperative period and in the long term means the resolution of cardiovascular symptoms with the adequate positive remodelling of the right chambers. Funding Acknowledgement: Type of funding sources: None.